Design And Characterization Of Gas Powered System Of Zidovudine Using Synthetic Polymers - N. G. RAGHAVENDRA RAO,; SHRISHAIL M. GHURGHURE,; MANGESH MUNDE,; ABDUL HADI., (International Journal of Pharma and Bio Sciences, 2011)
Zidovudine is the first approved compound for the treatment of AIDS, and having short biological half-life and poor bioavailability. The present research work an attempt has been made to design the Zidovudine gas powered drug delivery system for controlled release. The gas powered tablets were prepared by direct compression. The sodium bicarbonates and citric acid were also used as a gas generating agent. Drug compatibility with excipients was checked by FTIR and DSC studies. No chemical interaction between drug and excipients was confirmed. The prepared gas powered tablets are evaluated to post-compressional parameters. In all the formulations, the post-compressional parameters evaluated were within prescribed IP limits. The floating lag time of the prepared formulations is good except for two formulation F1 and F2 and the floating time for all the formulations was >16 hrs except F1 and F2 which does not float at all. The results of lag time study and floating time, the values of floating lag time ranges from 5 to 20 min, and floating time ranges from 180-1440 min. The formulation F8 shows the lag time 5 min and buoyancy time >1440 min. Drug release kinetics was studied for prepared formulations, results were found to follow zero order kinetics. The stability study conducted as per the ICH guidelines and the formulations were found to be stable. From this study, it is concluded that, the formulations retained for longer period of time in the stomach and provides controlled release of the drug. Hence it may increasing the bioavailability of the drug and patient compliance.